2011
DOI: 10.1590/s1676-26492011000400007
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the use of an omega 3 and omega 6 combination(EquazenTM) in paediatric patients with refractory epilepsy

Abstract: INTRODUCTION: Epilepsy is considered a health problem. 85% of patients are satisfactorily controlled with antiepileptic drugs (AEDs) and 15% have refractory seizures. The combination of omega 3 and omega 6 fatty acids (EquazenTM) can contribute to changes in ionic currents and to stabilization of neurotransmitter's function resulting in cell membrane equilibrium. These changes lead to potential seizure control. OBJECTIVE: To compare efficacy and safety in the treatment of refractory epilepsy with a supplement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Several studies have been shown that omega-3 fatty acids reduce neuronal excitability and may be useful in the non-pharmacological treatment of patients with epilepsy [16]. shown an inverse association between omega-3 supplementation and frequency and severity of seizure [12,[17][18][19], however, in some studies these effects were not observed [20,21] (Table 1). In the non-randomized open labeled trial EPA and omega 3 supplementation in 10 patients with chronic epilepsy has not significant effect on epilepsy [22].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been shown that omega-3 fatty acids reduce neuronal excitability and may be useful in the non-pharmacological treatment of patients with epilepsy [16]. shown an inverse association between omega-3 supplementation and frequency and severity of seizure [12,[17][18][19], however, in some studies these effects were not observed [20,21] (Table 1). In the non-randomized open labeled trial EPA and omega 3 supplementation in 10 patients with chronic epilepsy has not significant effect on epilepsy [22].…”
Section: Introductionmentioning
confidence: 99%